PSYCHOLOGICAL WELL BEING, PERILAKU PROSOSIAL PADA DEWASA AWAL - Fitriana Fatmawati Supratikno; Ardianti Agustin (Fakultas Psikologi Universitas Wijaya Putra, 2020)
This study aims to determine whether there is a relationship between psychological well being and prosocial behavior. This research was conducted in West Surabaya, with the research subjects were 100 early adult individuals. The sampling technique used in this study was incidental sampling. The data collection tool was in the form of a questionnaire in the form of google form consisting of 41 items of psychological well being statements and 47 items of prosocial behavior statements. Data analysis was performed using Pearson's product moment correlation statistical technique, with the help of SPSS for Windows Ver 2.1. From the results of the research analysis, the correlation value between psychological well being and prosocial behavior was 0.517 and p was 0.197 with a sig (2-tailed) value of 0.000. Compared with the significance level of 0.05 (5%), the sig (2-tailed) value is smaller, which means that there is a relationship between psychological well being (X) and prosocial behavior (Y) in early adult individuals in West Surabaya.